The Shanghai Cooperation Organization’s Development Dynamics - V. S. Lavrov (Московский журнал международного права)
The article is focused on examining legal aspects of the (SCO) and its characteristics as a regional international organization. Particular attention is devoted to examining statutory documents, legal norms and regulations formulated within the SCO, as well as to the analysis of structure, composition and functioning of various working bodies within the Organization.The author points out that besides growing political impact on regional affairs the SCO displays dynamic institutional development and has significantly broadened the scope of interstate multilateral cooperation within the Organization both on regional security issues and economic matters.